Computational Analysis of 47/49Ti NMR Shifts and Electric Field Gradient Tensors of Half‐Titanocene Complexes: Structure–Bonding–Property Relationships. Issue 36 (26th July 2013) - Srebro, Monika; Autschbach, Jochen
Abstract Metal NMR shielding and electric‐field gradient (EFG) tensors are examined by quantum‐chemical calculations for a set of 14 titanium(IV) complexes. Benchmarks are performed for titanocene chlorides that have been characterized recently by solid‐state NMR experiments, focusing on the dependence of TiIV NMR parameters on the computational model in terms of the choice of the density functional, and considering molecular clusters versus infinite‐periodic solid. Nearest‐neighbor and long‐range effects in the solid state are found to influence NMR parameters in systems without spatially extended ligands. Bulky ligands increase the fraction of local structure and bonding information encoded in the EFG tensors by reducing intermolecular interactions. Next, Ti shielding constants and EFG tensors for a variety of olefin (co)polymerization catalysts are analyzed in terms of contributions from localized molecular orbitals representing Lewis bonds and lone pairs. Direct links between the observed theoretical trends and the local bonding environment around the Ti metal center are found. A specific dependence of the Ti EFG tensors on the exact arrangement and type of surrounding bonds is demonstrated, providing a basis for further studies on solid‐supported titanium catalytic systems.